2023
DOI: 10.1186/s12967-023-04536-2
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 2 as a novel prospective tumor suppressor induced by ERG promotes ubiquitination-mediated radixin degradation to inhibit gastric cancer tumorigenicity and metastasis

Xiaocheng Tang,
Jintuan Huang,
Yingming Jiang
et al.

Abstract: Background Gastric cancer (GC) is a fatal cancer with unclear pathogenesis. In this study, we explored the function and potential mechanisms of intercellular adhesion molecule 2 (ICAM2) in the development and advancement of GC. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were performed to quantify ICAM2 expression in harvested GC tissues and cultured cell lines. Immunohistochemical analyses were conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Following this, the urea concentration was reduced to 2 M by adding 563 μL 100 mM ABC buffer, and the samples were subjected to additional digestion with trypsin at a 1:100 enzyme-to-substrate ratio (0,55 μg Trypsin for 55 μg protein) overnight at 37°C. After digestion, salts and detergents were removed before LC-MS analysis by SDB-RPS StageTips (Empore™ 2241) as described previously 25 . Eluted peptides were dried by vacuum centrifugation and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, the urea concentration was reduced to 2 M by adding 563 μL 100 mM ABC buffer, and the samples were subjected to additional digestion with trypsin at a 1:100 enzyme-to-substrate ratio (0,55 μg Trypsin for 55 μg protein) overnight at 37°C. After digestion, salts and detergents were removed before LC-MS analysis by SDB-RPS StageTips (Empore™ 2241) as described previously 25 . Eluted peptides were dried by vacuum centrifugation and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although the exact molecular mechanism has not been fully clarified yet, it may facilitate the development of new anticancer strategies [124]. Xiaocheng Tang et al revealed that intercellular adhesion molecule 2 (ICAM 2) was significantly downregulated in GC cells and tissues and could be used to evaluate prognoses, and that ICAM 2 promoted the ubiquitination degradation of radixin (RDX) in a NEDD4L-dependent manner to inhibit GC cell proliferation and migration [88]. Overall, the above evidence suggests that NEDD4 and NEDD4L are involved in the development of GC via a variety of signaling pathways, but some of the molecular mechanisms are still uncertain and require further study (Figure 3) (Table 1).…”
Section: Nedd4/nedd4l Inmentioning
confidence: 99%
“…The rate of intercellular adhesions differs between cancer cells and normal cells. 48,58 The collective dynamics and activity of cells in thick tissue, which can be connected to embryonic development, are to blame, 49 including in wound healing 59 and cancer. 60 The epithelial and mesenchymal transition was seen in vivo as a solid–liquid transition phase where cell mobility increases and adhesion diminishes, and this has been shown to play a significant role in tissue healing, inflammation, and tumor growth.…”
Section: Elasticity Relationship With Mechanical Cellular Propertiesmentioning
confidence: 99%